Uncertainty factors in supply chains - Járvás, Tamás; Illés, Béla; Bányai Tóth, Ágota (Advanced Logistic Systems - Theory and Practice, 2025)
Increasingly diversified consumer needs force market players into a competitive situation where the optimal design and operation of the entire supply chain becomes essential for survival and economic efficiency. This can only be achieved if the elements of the supply chain can respond to changing environmental conditions as quickly as possible. One of the biggest challenges to the optimal operation of supply chains, as a consequence of globalization, is uncertainty. In recent years, we have witnessed how a natural disaster or a pandemic can cause significant disruptions in the operation of supply chains, compelling companies to recognize the importance of stable supply chains. This article examines the impact of these uncertainty factors on the operation of supply chains and aims to explore the possibilities for identifying and managing risks.